Legislating Climate Change: Australia’s Renewable Energy Target Legislation Examined by a Solar Farmer - Fullarton, Alexander (2019)
This paper examines the concept of sustainable development and the need to consider its ‘three pillars’ – the social, economic and environmental impacts – as one interrelated concept: the triple bottom line (TBL). The rationale of the TBL is that no single influence can exist in isolation for an indeterminate period of time. An imbalance between the three overarching factors, favouring one over the interests of the other two, will adversely affect the others and ultimately itself. An enterprise focussed solely on profit, at the expense of society and the environment, will not be able to be sustained indefinitely. This paper focuses on the impact of carbon emissions caused by industrialisation, and its reliance on fossil fuelled energy sources. It briefly examines how the carbon cycle functions and successive Australian governments’ legislative attempts to address carbon emissions to mitigate the impact of greenhouse gases on global warming. Finally, it places the impact of those legislative requirements on industry to dilute carbon emissions with energy sourced from renewable sources in the context of how the Solex solar farming project in Carnarvon Western Australia receives economic benefits from that legislative intervention to encourage renewable energy-based industry. The Solex project competes directly with fossil fuelled industry to manufacture and market its products.